Explored Jordanian Math Teacherâ€™s Practices, and Belief Change in implementing mobile applications in education - Khaled Ahmed Aqeel Alzubi (AT-TA'LIM, 2021)
The aim of This study explored Jordanian math teachersâ€™ beliefs, practices, and belief change in implementing mobile applications in education Learning mathematics is a major focus of educational institutions at all levels and technology has long been an important teaching tool in the field of mathematics. Multiple sources of qualitative data were generated including metaphors, lesson plans and interviews with 17 math teachers. Although teachers considered Implementing mobile applications in education as an effective method that benefit student learning and they demonstrated progress in changing their beliefs moving from subject to didactic dimension through Implementing mobile applications in education, their practices remained partially aligned with their perceived belief changes. This discrepancy could be attributed to several encountered challenges, including teachersâ€™ lack of confidence, difficulty in facilitating student collaboration, structural constraints, additional workload, and the lack of school and peer support. Results suggest the need for different types of â€œproblemsâ€ and approaches such as more direct instruction, and higher feasibility in teachersâ€™ autonomy when Implementing mobile applications in education. Outcome of this study has a few implications. First, discrepancy between belief and practice of implementing mobile applications. identified in this study suggests that appropriate and sufficient professional development activities are needed. The MOE and schools in Jordan should further articulate policy goals and standards that facilitate student-centered approaches for teachers. System and institutional supports such as reducing teachersâ€™ workload, providing sufficient time for studentsâ€™ activities during implementing mobile applications. sessions and for teachersâ€™ collaboration, and involving both students and teachers in defining.